Fiscal Decentralization and Welfare Spending in Indonesian Local Governments: Women's Participation as a Moderator - Riska Venni; Yulianti Abbas (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to examine the relationship between fiscal decentralization and welfare spending and to investigate the moderating role of women’s participation in strengthening the relationship between fiscal decentralization and welfare spending in local governments. Research Methodology: This study employs panel data from 466 district and city governments in Indonesia during 2022–2023. Fiscal decentralization is measured using the Budget Realization Report (LRA) and Operational Report (LO), while the proposed relationships are examined using moderated regression analysis. Results: The findings reveal that fiscal decentralization, measured through LRA and LO indicators, has a positive and significant effect on welfare spending. However, women’s participation does not significantly moderate this relationship, indicating that numerical representation alone does not necessarily improve the effectiveness of fiscal policies in supporting welfare allocation. Conclusions: The study confirms that stronger fiscal decentralization contributes to increased welfare spending at the local government level. Nevertheless, women’s participation has not demonstrated a significant role in enhancing the impact of fiscal decentralization on welfare outcomes. Limitations: This study is limited by the short observation period, focus on Indonesian local governments, and quantitative measurement of women’s participation, which may not fully capture its quality and influence. Contributions: This study contributes to fiscal decentralization and public governance literature by demonstrating the importance of fiscal capacity in welfare spending and emphasizing the need to consider the quality of women’s participation in public decision-making.